Influence of rumen bypass fat in cattle supplements on forage utilization - Hightshoe, R.B.; Cochran, R.C.; Corah, L.R.; Harmon, D.L.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Incorporation of rumen bypass fat into a supplement to be fed with low quality forage did not affect total dry matter digestibility or ruminal dry matter fill. Similarly, no difference in digestibility was observed among types (animal vs. plant) or levels (low vs. high) of lipids used in this study. Rumen bypass fat apparently avoids the negative impact on forage utilization seen with conventional fats.
Keywords: Beef; Rumen; Forage; Supplements